INFLUENCE OF ENTREPRENEURSHIP KNOWLEDGE AND ENTREPRENEURIAL SELF-EFFICACY ON ENTREPRENEURIAL INTENTION: THE MEDIATING ROLE OF ENTREPRENEURIAL ATTITUDE IN EAST JAKARTA CULINARY SMES - Keren Sarwana Kho; Rodhiah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
A strong entrepreneurial foundation is essential for sustaining business growth, especially in the highly competitive culinary industry. The culinary sector is one of Indonesia’s most dynamic creative economy subsectors, yet many businesses face intense competition and a high risk of failure. This condition highlights the importance of understanding psychological and behavioral factors that influence entrepreneurs’ decision-making. Therefore, this study aims to analyze the effect of entrepreneurship and entrepreneurial self-efficacy on entrepreneurial intention, with entrepreneurial attitude serving as a mediating variable among culinary entrepreneurs in East Jakarta. The research employed a quantitative approach using a cross-sectional design, with a sample of 291 culinary entrepreneurs selected through purposive sampling. Data were collected through Likert-scale questionnaires distributed directly to respondents and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings reveal that entrepreneurship and entrepreneurial self-efficacy both have a positive and significant influence on entrepreneurial intention. In addition, both variables also positively affect entrepreneurial attitude. This study further confirms that entrepreneurial attitude plays a mediating role in the relationship between entrepreneurship and entrepreneurial intention, as well as between entrepreneurial self-efficacy and entrepreneurial intention. These results offer meaningful insights into how psychological readiness, confidence, and entrepreneurial orientation can strengthen entrepreneurial intention among culinary entrepreneurs. The findings also provide practical guidance for policymakers and business development programs in designing initiatives that enhance the sustainability and competitiveness of culinary businesses in East Jakarta.